Analysis of the Development of Downstream Copper Industry in Indonesia to Obtain Maximum Added Value Using Dynamic Systems - Oetomo, Dedy Setyo; Dewi , Eki Kania; Ramdhani, Rizky Fajar (Journal of Information System, Technology and Engineering, 2024)
This research aims to design a dynamic system model for the downstream copper processing industry. The secondary data obtained is data provided by the BKPM Strategic Investment Downstreaming Expert Team. Vensim software is used to simulate downstream development in the form of CLD and SFD from 2024 to 2045. The results of the value-added simulation resulted in an increase in the added value of copper cathode by 2.15 times, the added value of cathode slab by 1.62 times, the added value of copper billet by 1.65 times, the added value of copper bar &rods by 1.08 times, the added value of copper tube by 1.02 times, the added value of copper strip by 1.39 times, and the added value of copper wire by 1.58 times. After a sensitivity analysis of the selling price at CAGR and an increase in energy costs by 20%, there was a change in the average value-added margin, so that the increase in added value changed which resulted in an added value of copper cathode of 1.9 times, added value of cathode slab of 1.47 times, added value of copper billet of 1.49 times, added value of copper bar &rods of 1.26 times, added value of copper tube of 0.93 times, added value of copper strip of 0.98 times, and added value of copper wire of 1.44 times.